Analisis Kebutuhan Flipbook-Augmented Reality Berbasis Kearifan Lokal - Apriza Fitriani; Rukiah Lubis (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to analyze students' needs for augmented reality flipbooks based on local Bengkulu wisdom. This type of research is Research and Development (R&D) using the Plomp model, but this research is limited to the preliminary research stage. Data collection was carried out by giving questionnaires to lecturers and all active students in the biology education study program. The student needs analysis questionnaire includes four indicators, then the data obtained is analyzed through qualitative descriptions. The research results show, a) 94% of the lecture system uses a face-to-face (offline) system and 6% uses a hybrid learning system; b) learning resources used by students and lecturers in the lecture system, namely 40% and 47% using the internet, 39% and 35% printed books; c) the use of teaching media in the lecture process showed that 82% answered yes and 18% no; d) students' knowledge about local wisdom in Bengkulu, 35% answered the Rafflesia flower, 25% Kaba Hill and Waterfall; e) as many as 82-86% of students and lecturers do not know about augmented reality flipbooks based on local wisdom, 14-18% know about augmented reality flipbooks; f) 100% of lecturers and students responded that it was necessary to develop augmented reality flipbooks based on local wisdom in the hope that the lecture process would become more innovative. In conclusion, it is necessary to develop an augmented reality flipbook based on Bengkulu local wisdom as a learning resource for the lecture process, especially in the Biology education study program. Keywords: Analysis, Augmented Reality, Flipbook, Local Wisdom, Students